The school counselor's guide to special education - Trolley, Barbara C. 4 0 16; Haas, Heather S.,;Patti, Danielle Campese; 5 (Thousand Oaks, California : Corwin Press, 2009)
A practical guide for school counselors that help them assist students with special needs, covering topics including assessment and intervention, individual and group counseling, behavioral and academic challenges, and legal and ethical issues.
Includes bibliographical references.
Professional.
Keywords: 2 -- 0; 6; Counseling in special education;Special education;Counseling in special education;Special education -- Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc; 20; 2